Employment stability of entrants in newly founded firms: a matching approach using linked employer-employee data from Germany - Claus Schnabel; Susanne Kohaut; Udo Brixy (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2008)
Using a linked employer-employee dataset and taking the perspective of individuals rather than firms, this paper analyzes some effects of joining start-ups. We show that entrants in new firms differ from those joining incumbent firms, and we use a matching approach to compare a group of employees joining new firms in 1995/96 with a control group entering incumbent firms. Our results indicate that individuals' employment stability was higher in incumbent than in newly founded firms while their risk of becoming unemployed was lower. In particular in eastern Germany, joining firms that were older than six years was the best strategy. – – Diese Arbeit analysiert unter Verwendung eines verbundenen Arbeitgeber-Arbeitnehmer-Datensatzes einige Auswirkungen des Eintritts in Neugründungen, wobei die Sicht von Individuen statt von Firmen eingenommen wird. Wir zeigen, dass Personen, die in neue Firmen eintreten, sich von Eintreten-den in bestehende Firmen unterscheiden, und wir verwenden einen Matching-Ansatz, um eine Gruppe von Personen, die 1995/96 in Neugründungen eintrat, mit einer Kontrollgruppe von Eintretenden in bestehende Firmen zu vergleichen. Unsere Ergebnisse deuten darauf hin, dass die Beschäftigungsstabilität der eintre-tenden Personen in bestehenden Firmen höher als in Neugründungen ausfiel, während ihr Risiko arbeitslos zu werden geringer war. Insbesondere in den neuen Bundesländern bestand die beste Strategie darin, in Firmen einzutreten, die älter als sechs Jahre waren.
Keywords: J63; J64; 330; employment; unemployment; newly founded firma; linked employer-employee data; Germany; Arbeitsmobilität; Unternehmensgründung; Arbeitsplatzsicherung; Deutschland; Neue Bundesländer